Impact of Indonesia Presidential Election Quick Count on Political Connected Stock Volatility: An Event Study - Hardiansyah, Hardiansyah (Dinasti Publisher, 2024)
This study assesses the impact of the 2024 Indonesia Presidential Election quick count results on the stock volatility of politically connected firms listed on the Indonesia Stock Exchange. An event study methodology is employed, analyzing four politically affiliated companies—PMMP, TOBA, BRMS, and WIRG—across a six-day event window (T-3 to T+3). A market-adjusted return model calculated abnormal returns (AR) and cumulative abnormal returns (CAAR). The findings reveal a significant market reaction before the event, particularly on T-2, where the average abnormal return (AAR) peaked at 5.82%, mainly driven by PMMP’s strong return of 16.66%. However, the AAR fell sharply to -3.91% on T+3, indicating a market correction. The cumulative abnormal return (CAAR) reached a high of 6.63% on T-2 before declining to 1.48% on T+3. A T-test yielded a p-value of 0.092 at a 10% significance level, showing a statistically weak significance in pre-and post-event returns. While the quick count results impacted stock performance, the market reaction was moderate. This study provides valuable insights for investors, helping them understand the influence of political uncertainty on politically connected firms in emerging markets and make informed investment decisions.